THE COGNITIVE DEMANDS OF SIMULTANEOUS INTERPRETATION IN PUBLIC SPEECHES: CHALLENGES AND SOLUTIONS - Muminova Ziyoda; Axmedova Anorxon; Axmedova Anorxon (Лучшие интеллектуальные исследования, 2023)
Annotation: Simultaneous interpretation in public speeches presents a unique set of cognitive challenges for interpreters. This article explores the cognitive demands inherent in this complex task, analyzes existing literature on the subject, discusses various methods employed by interpreters, presents research findings on the results of these methods, and concludes with insights into the future of simultaneous interpretation.